Seas of Renewal: Turning Sea Urchin Waste into Polyhydroxynaphtoquinone-Collagen Biomaterials for Regenerative Medicine - Giordana Martinelli; Stefania Marzorati; Margherita Roncoroni; Luciano Magro; Matteo Brilli; Giangiacomo Beretta; Graziano Colombo; Luca Melotti; Anna Carolo; Giulia Zivelonghi; Stefano Farris; Marco Patruno; et al. (Marine Biotechnology, 2025)
Chronic wounds and skin ulcers pose significant challenges to healthcare systems globally, necessitating innovative approaches to accelerate healing processes. Biomaterial-based therapies have emerged as promising solutions for tissue regeneration. This study focuses on valorization of sea urchin waste toward the development and characterization of collagen-based scaffolds added with polyhydroxynaphthoquinone (PHNQ) antioxidants, successfully incorporated into biomaterials at optimal ratio, enhancing scaffold stability and integrity. Water uptake, mechanical properties, and degradation kinetics of the composite scaffolds were evaluated and compared with controls. Biocomposites were also tested for cytotoxicity. Results indicate that composite scaffolds exhibit superior chemical stability and slower degradation rates, attributed to strong interactions between collagen and PHNQs. This aspect was explored also through in silico investigations by means of tight binding molecular dynamics methods. It has been found that a covalent bond forms between the selected collagen representative and one PHNQ. Furthermore, the antioxidant activity of PHNQs was retained in the composite scaffolds, providing additional therapeutic benefits under the perspective application of regenerative medicine. Normal human dermal fibroblasts (NHDF) exposed to the combination of collagen and PHNQs remained viable. Overall, these findings highlight the potential of sea urchin food waste in a valorization chain, offering added value through the production of collagen-based composite scaffolds.